Surgical Outcome Measures in a Cohort of Patients at High Risk of Breast Cancer Treated by Bilateral Risk-Reducing Mastectomy and Breast Reconstruction. Issue 3 (24th June 2022) - Gandhi, Ashu; Duxbury, Paula; Clancy, Tara; Lalloo, Fiona; Wisely, Julie A.; Kirwan, Cliona C.; Foden, Philip; Stocking, Katie; Howell, Anthony; Evans, D. Gareth
Abstract : Background: Women with breast cancer–related genetic pathogenic variants (e.g., BRCA1, BRCA2 ) or with a strong family history carry lifetime risks of developing breast cancer of up to 80 to 90 percent. A significant proportion of these women proceed to bilateral risk-reducing mastectomy. The authors aimed to document the surgical morbidity of risk-reducing mastectomy and establish whether a diagnosis of breast cancer at the time of surgery impacted outcomes. Methods: Clinical details of 445 women identified as having a greater than 25 percent lifetime risk of developing breast cancer who underwent risk-reducing mastectomy and breast reconstruction were interrogated for surgical outcomes such as planned, unplanned, and emergency procedures; complication rates; length of stay; and longevity of breast reconstruction. These outcome measures were recorded in women diagnosed with breast cancer perioperatively (cancer group) and those without malignancy (benign group). Results: Median follow-up was similar in both groups (benign group, 70 months; cancer group, 73 months). Patients were older in the cancer group than in the benign group (43 years versus 39 years; p < 0.001). Women in the cancer group required more planned procedures to complete reconstruction than those in the benign group (four versus two; p = 0.002). Emergency procedures, unplanned surgical interventions (e.g., capsulectomy), and postreconstruction complication rates were similar between groups. One in five women overall required revision surgery. Patients with autologous reconstructions had a revision rate of 1.24 per 1000 person-years compared with 2.52 per 1000 person-years in the implant reconstruction group. Conclusions: Women contemplating risk-reducing mastectomy can be reassured that this is a safe and effective procedure but will likely take multiple interventions. This knowledge should be integral to obtaining informed consent. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.